Aeroelastic load control of large and flexible wind turbines through mechanically driven flaps - Wei, Xing (2020)
The load reduction of the wind turbine through the use of flaps actuated through novel mechanical network is studied. The aeroservoelastic model of the wind turbine couples the composite beam description for blades and tower to the unsteady vortex-lattice method for the aerodynamics. The trailing-edge flap dynamics are incorporated to the wind turbine model to enable the use of mechanical network to control the flap rotation. A passive mechanical controller is proposed, which senses the relative angular velocity of the trailing-edge flap and generate the control torque. The mechanical controller is realised by passive components including springs, dampers and inerters in rotational form. The parameters of the mechanical components and flap configuration parameters are optimised by H∞ and H2 optimisation, respectively. It is shown that mechanical controllers exhibit marked reductions in blade root-bending moment, blade tip deflection and tower top fore-aft deflection in the presence of external disturbances, especially with the optimised flap configuration parameters.